ANALISIS REKSADANA SYARIAH DALAM KONSEP NILAI AKTIVA BERSIH (NAB) - Tania, Atika Lusi (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2016)
Mutual fund composed of two concepts, namely mutual meaning keep or keep and the concept of the Fund means the set of money. Mutual funds means a collection of money is kept. Mutual funds (mutual fund) is a vehicle used to gather a Community Fund (financiers) to then be invested into the portfolio effect by investment managers (MI). The effect can be a portfolio of stocks, bonds, money market instruments, or a combination of some of these capital market law No. 8 year 1995 article 1, paragraph (27): "mutual fund is a container used to gather funds from society to next Financiers invested in the portfolio Effect by investment manager." On mutual funds, investment management manages funds that they are placed in securities and realize gains or losses and receive dividends or interest are dibukukannya into the Net Assets Value (NAV) of the Fund. Wealth funds managed by the investment manager to the custodian bank is stored on is not affiliated with the investment manager, the custodian bank which is what will act as administrator of a collective and daycare. Shariah-compliant mutual fund is a container used to gather funds from community of property owners as a financier (shabib al-mal/rabb al-mal) to next invested in the Portfolio Effect by the investment manager as a representative of shahib al-mal according to the provisions and principles of the Shariah.Keywords: Â Islamic mutual fund, investment, portfolio